Pengaruh Kualitas Produk dan Ketersediaan Produk Terhadap Keputusan Pembelian dengan Citra Merek Sebagai Variabel Intervening (Studi Pada Konsumen Minuman Energi M-150 di Kota Semarang) - Apriando, Joni Putra; Soesanto, Harry; Indriani, Farida (Master of Management Diponegoro University, 2019)
The increasing development of the business world has reached a higher level of competition, and increasingly fierce competition in the energy drink market in Indonesia. This can be seen from the renewal of the company, which makes energy beverage products become consumers' choice. One of the producers of energy drinks that compete in Indonesia is the M-150. Currently the energy drink product M-150 is still one of the products that consumers choose. However, along with the increase in other products, making the M-150 product more and less competitive with other products. This can be seen in the top brand index where the M-150 product is no longer a superior product for consumers. Formulation of the problem in this study concerning the influence of product quality and assessment of brand image, as well as its impact on purchasing decisions of M-150 products in the city of Semarang.The population used in this study is all consumers who have done the purchase of M-150 energy products, where the respondents are people in the city of Semarang. The number of samples used in this study were 130 respondents, and the sample technique used was accidental sampling. The data source used is primary data, while the method of data collection is done through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques using AMOS 22.0 analysis tools.The results of the research analysis show that brand image has a positive and significant effect on purchasing decisions, product quality has a positive and insignificant effect on purchasing decisions, product quality has a positive and significant effect on brand image, product availability has a positive and significant effect on purchasing decisions, and availability product has a positive and not significant effect on brand image.